Repensar los estudios sobre saberes indígenas: A propósito del caso p'urhépecha. Issue 2 (3rd April 2022) - Rea Campos, Carmen Rosa; Martínez Rodríguez, Marcela
ABSTRACT: The article tries to carry out a critical review on the conception that ethnobiological and anthropological studies sustain regarding the relationship between indigenous knowledge and the environment, taking as a particular case the studies on knowledge of the P'urhépecha, people settled in Michoacán, Mexico. Without denying the advances regarding the field of indigenous knowledge, there are three problematic axes presented by the analyzed works: the tendency to naturalize knowledge and the indigenous-nature relationship; to reify indigenous knowledge a whose singularity and opposition to western knowledge lies in you immunity to social change; lastly, the difficulties of making visible the power relations that mediate the production and reproduction of knowledge, where indigenous peoples as agents confront, with other internal or external agents, in a struggle for meaning, appropriation and control of processes of validity of knowledge and truth, in contexts of social change and environmental deterioration.